(untitled) (Cardiovascular Journal, 2020)
Background: This is a prospective observational single center study to determine whether bridging anticoagulation with heparin along with warfarin is mandatory in a heterogenous group of patients undergoing valve replacement surgery either single or multiple valve (with mechanical or tissue valve) in the post-operative period. Methods: Perioperative data were collected in 41 patients undergoing multiple valve replacement at this center from July/2019 to September/2019 irrespective of age, sex, number and type of valve replaced. No bridging anticoagulation was given in preoperative and postoperative period in these patients. They were prospectively observed for the incidence of any thromboembolic end bleeding events with daily measurement of International Normalized Ratio (INR) till INR reached at therapeutic level for oral anticoagulant warfarin and complications of warfarin therapy. Results: All the patient suffered from chronic Rheumatic heart disease. Single valve disease was in 70.73% and multiple valve disease was in 29.27% cases. Two patients had left atrial thrombus, seven patient (14.63%) had preoperative atrial fibrillation (AF). Postoperative new onset AF was present in 10 (24.39%) cases. No thromboembolism occurred in these patients and warfarin over anticoagulation was found in 1/41 patient. Conclusion: Patients undergoing valve replacement surgery without concomitant postoperative bridging anticoagulation with heparin do not suffer from any thromboembolic and bleeding complications even at lower level of INR. This study also shows that single and multiple valve (both mechanical and tissue valve) have the same in hospital outcome in relation to thromboembolism and bleeding complications. Cardiovasc. j. 2020; 13(1): 27-34